2020
DOI: 10.1055/a-1343-1597
|View full text |Cite
|
Sign up to set email alerts
|

Optical diagnosis of colorectal polyp images using a newly developed computer-aided diagnosis system (CADx) compared with intuitive optical diagnosis

Abstract: Background: Optical diagnosis of colorectal polyps (CRPs) remains challenging. Imaging enhancement techniques such as narrow band imaging and blue light imaging (BLI) can improve optical diagnosis. We developed and prospectively validated a computer-aided diagnosis system (CADx) using high definition white light (HDWL) and BLI images, and compared it with the optical diagnosis of expert and novice endoscopists. Methods: The CADx characterized CRPs by exploiting artificial neural networks. Six experts and thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…In a prospective study by van der Zander et al [ 66 ], CADx diagnostic performances using high-definition white-light (HDWL) and blue-light imaging (BLI) were compared to those of optical diagnosis by expert and novice endoscopists using the BLI Adenoma Serrated International Classification (BASIC) [ 67 ]. The accuracy of AI was 88.3% using HDWL images, 86.7% using BLI images, and 95.0% using both, performing better than experts (81.7%, p = 0.03) and novices (66.7%, p < 0.001).…”
Section: Lower Gastro-intestinal Tractmentioning
confidence: 99%
“…In a prospective study by van der Zander et al [ 66 ], CADx diagnostic performances using high-definition white-light (HDWL) and blue-light imaging (BLI) were compared to those of optical diagnosis by expert and novice endoscopists using the BLI Adenoma Serrated International Classification (BASIC) [ 67 ]. The accuracy of AI was 88.3% using HDWL images, 86.7% using BLI images, and 95.0% using both, performing better than experts (81.7%, p = 0.03) and novices (66.7%, p < 0.001).…”
Section: Lower Gastro-intestinal Tractmentioning
confidence: 99%
“…dedicated convolutional neural network (CNN)-based artificial intelligence (AI) systems. In this issue of Endoscopy, van der Zander et al present a study on a novel CNN-based AI system for polyp characterization [6]. The authors showed that, by combining high-definition white-light and blue-light imaging (so-called multimodal imaging), the AI overall diagnostic accuracy was impressive (95.0 %), and higher than that of both experts (81.7 %) and novices (66.7 %).…”
mentioning
confidence: 99%
“…As reported in the study by Mori et al [7], within a clinical framework and according to the Preservation and Incorporation of Valuable endoscopic Innovations (PIVI) statements [1], the main outcome of any AI validation study should be clinically oriented. For this purpose, the study by van der Zander et al [6] appears largely underpowered. Second, a tool for everyday clinical practice should demonstrate good discriminatory performance for every polyp histology.…”
mentioning
confidence: 99%
See 2 more Smart Citations